2022
DOI: 10.1080/10717544.2022.2086940
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of the engagement of inorganic nanomaterials in cancer immunotherapy

Abstract: Cancer has attracted widespread attention from scientists for its high morbidity and mortality, posing great threats to people’s health. Cancer immunotherapy with high specificity, low toxicity as well as triggering systemic anti-tumor response has gradually become common in clinical cancer treatment. However, due to the insufficient immunogenicity of tumor antigens peptides, weak ability to precisely target tumor sites, and the formation of tumor immunosuppressive microenvironment, the efficacy of immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Inorganic nanomaterials are the easiest to manufacture and can be classified as metals, semiconductors, and nonmetals such as gold, silver, silicon dioxide, titanium dioxide, rare earth oxides, iron oxide, zinc oxide, and quantum dots [54]. These have received widespread attention in biomedicine due to their unique size and properties, including their optical, electrical, and magnetic characteristics [55].…”
Section: Inorganic Materials Nanoparticle Delivery Systemmentioning
confidence: 99%
“…Inorganic nanomaterials are the easiest to manufacture and can be classified as metals, semiconductors, and nonmetals such as gold, silver, silicon dioxide, titanium dioxide, rare earth oxides, iron oxide, zinc oxide, and quantum dots [54]. These have received widespread attention in biomedicine due to their unique size and properties, including their optical, electrical, and magnetic characteristics [55].…”
Section: Inorganic Materials Nanoparticle Delivery Systemmentioning
confidence: 99%
“…MSNs have great potential for use in the treatment of various diseases such as cancer, diabetes, and Alzheimer's disease. 44,45…”
Section: Mesoporous Silica Nanocompositementioning
confidence: 99%
“…Additionally, various immune checkpoints are modulated with different formulations of inorganic NPs. Comprehensive research studies have shown that aluminum oxide NPs can upregulate the expressions of CD80, CD86, MHC-1, and MHC-2 molecules in dendritic immune cells [127]. The overexpression of these checkpoint molecules stimulates the secretion of interferon-γ to inhibit tumorigenic growth.…”
Section: Modern Radiotherapymentioning
confidence: 99%